Spontaneous resorption of an insect hair in the corneal stroma: A case report - Somsanguan Ausayakhun (2018)
A case of keratitis, due to an insect hair penetrating into the deep cornea, was reported. The patient felt right ocular pain while riding a motorcycle, as an insect struck into his eye. On examination, an insect hair was seen embedded into the corneal stroma with severe corneal edema, which caused a visual acuity of the right eye decreased to hand motion. The patient was treated by a topical antibiotics, cycloplegics, and anti-inflammatory drugs, without removing the hair. After a 6-week follow-up period, there was a spontaneous resorption of the hair. There was no apparent toxic sign during 6-months of follow up, and the visual acuity improved to 6/6. The insect hair could be left in the deep cornea with careful observation, and spontaneous resorption can occur.